Great games that disappeared - Rauschenbach, James; Swartz, Daniel R (Strategies: a journal for physical and sport educators, 2016)
Sometimes through a single person's efforts, a new and innovative game is developed and promoted locally. Occasionally, circumstances cause these games to remain on a local level without being adopted by mainstream physical educators and physical activity professionals. Unfortunately, some educators tend to stick to what they know and teach traditional games and sports. This practice has left little room for unique and innovative games such as tchoukball and hocker to contribute to physical education curriculum. This article describes the history of how each of these games was developed and promoted. Rules, equipment and game-play strategies are provided. ©, Copyright Taylor & Francis.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/100-180-565-266-823 tex.type: [object Object]
Keywords: dept.hms

“The greatest game ever”: swatball - Swartz, Daniel R; Rauschenbach, Jim (Strategies: a journal for physical and sport educators, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-715-466-336-656 tex.type: [object Object]
Keywords: dept.hms